INTEGRATIVE APPROACH TO TEACHING ENGLISH IN HIGHER EDUCATION INSTITUTIONS - Atabaeva Nodira Djuraevna; Mammadova Aygun Jahan (Bright Mind Publishing, 2025)
An integrative approach allows for the complex development of language skills, increasing student motivation and the formation of practical skills. This article explores the theoretical foundations and practical significance of an integrative approach to teaching English. The advantages of the integrative approach, methods of implementation and recommendations for teachers are also presented. The study is based on the analysis of literature dedicated to the integrative approach, the criteria for assessing its effectiveness and the experience of teachers who apply it in practice are studied. The article opens up the possibility of making the learning process more interesting, effective and practice-oriented by applying an integrative approach to teaching English.
Keywords: English, integrative approach, Language Teaching, communicative competence, task-based education, project-based education, content-based education, educational methods.